Need of Micronutrients in Dairy Cows - Aggarwal, Anjali (Indian Farming, 2015)
Supplementation of micronutrients in cows results in improved metabolic and immune status, increase in quality and quantity of milk and health of cows. Before supplementation for dairy cows, dairy farmers should get their animal feeds tested and their rations evaluated by a competent dairy cow nutritionist and a reliable laboratory to be sure of the required level of supplementation. While inadequate intake and absorption of certain nutrients may not give required results, supplementation above requirement can be expensive or in some cases toxic. Therefore, supplementation of micronutrients to cows is also economically beneficial in terms of increased profit from more milk production.